Deltoid Ligament Repair for Tibiotalar Stabilization and Reduction of Syndesmosis: A Cadaveric Study. Issue 3 (14th September 2018) - Butler, Bennet; Hempen, Eric; Muriuki, Muturi; Havey, Robert; Patwardhan, Avinash; Kadakia, Anish
Category: Ankle Introduction/Purpose: Ankle fractures with combined deltoid ligament/syndesmotic injuries are common. Proper reduction of these injuries may be deceptively difficult due to the complexity of the tibiotalar and syndesmotic articulations. The syndesmosis, in particular, has been shown to have a fairly high rate of malreduction with traditional techniques and intraoperative imaging. Additionally, the deltoid ligament has important contributions to tibiotalar alignment and stability which cannot be replaced with laterally based fixation alone. Deltoid ligament repair has the potential to address both of the proceeding issues, but has fallen out of favor due to a lack of clinical evidence supporting its use. Here we provide cadaveric data showing that deltoid ligament repair can assist with accurate syndesmotic reduction and stabilize the talus in all planes of motion. Methods: 21 lower limbs disarticulated at the knee were obtained for testing. A material testing machine capable of exerting known axial and rotational forces was utilized for testing. A motion capture system was used to accurately track the tibia, talus, and fibula in all planes of translational and rotational movement. The relative positions of each bone with respect to each other were tracked with the ankle hanging under gravitational forces only and with a modest axial force. This was done in intact ankles, ankles following creation of a combined deltoid ligament/syndesmotic injury state, and subsequently after deltoid ligament repair (Figure 1). Results: Compared to the intact state, after injury creation there was a significant increase in talar eversion with respect to the tibia when hanging which corrected with axial loading. Additionally, there was a significant increase in talar internal rotation with respect to the tibia with axial loading. Finally, there was a trend towards increased anterior translation of the fibula with respect to the tibia with axial loading which corrected with hanging. All of these rotational/translational issues were corrected with deltoid ligament repair. Conclusion: This study provides cadaveric evidence that after a combined deltoid ligament/syndesmotic injury, deltoid ligament repair can help ensure accurate syndesmotic reduction and stabilize the tibiotalar joint, especially with respect to inversion/eversion.